2009
DOI: 10.1017/s0022149x08201252
|View full text |Cite
|
Sign up to set email alerts
|

Soil-transmitted helminth infections in Nigerian children aged 0–25 months

Abstract: The objective of this cross-sectional study was to determine the prevalence and intensity of soil-transmitted helminths (STHs) in children aged 0-25 months and to identify the associated risk factors for Ascaris lumbricoides infections. The study was conducted in three villages outside Ile-Ife, Osun state, Nigeria in May/June 2005. Stool samples (369) were processed by formol-ether concentration. Ascaris lumbricoides (12.2%) was the dominant infection. Age, father's occupation and dog ownership were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 23 publications
4
22
1
Order By: Relevance
“…Also a prevalence of 40.5% and 40.7% among preschool age children and school age children, respectively, was reported in Kenya [10]. However, the prevalence of helminth infestation in the current study was relatively higher than other studies conducted in children in the Ashanti region (11.1%) of Ghana [11] and in Osun State in Nigeria (12.2%) [12]. The difference in prevalence could be attributed to timing of the study, sampling of study participants, seasonal differences in conducting the study, environmental conditions, and other geographical factors in these study areas.…”
Section: Discussioncontrasting
confidence: 66%
“…Also a prevalence of 40.5% and 40.7% among preschool age children and school age children, respectively, was reported in Kenya [10]. However, the prevalence of helminth infestation in the current study was relatively higher than other studies conducted in children in the Ashanti region (11.1%) of Ghana [11] and in Osun State in Nigeria (12.2%) [12]. The difference in prevalence could be attributed to timing of the study, sampling of study participants, seasonal differences in conducting the study, environmental conditions, and other geographical factors in these study areas.…”
Section: Discussioncontrasting
confidence: 66%
“…School-age children (2 to 5 years) had a higher prevalence of parasites compared to breast-fed infants (Table 3). Similarly, a study in Nigeria showed that children from 1 to 2.1 years had a higher risk of becoming infected with A. lumbricoides compared to children between 7 to 11 months old [26]. This may be due to the fact that school-age children tend to be more active, interact more with the environment by putting objects to their mouth with dirty hands (geophagy), and rarely adopt hygienic habits [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although school-aged children typically have a higher worm burden than preschool-aged children, PACs are still at risk for infection, as shown in our study and others. 3,[34][35][36] Very few studies have been done looking at the negative effects on growth and development in the PAC age group. However, given the rapid rate of development it is conceivable that infections in this age may be more deleterious to subsequent growth and cognitive development than infections suffered in later childhood.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] They are responsible for significant morbidity and mortality worldwide, causing an estimated loss of 39 million disability adjusted life years (DALYs). 5 This disability burden is greater than that due to malaria (35.7 million DALYs), 5 yet in comparison, STH are among the most neglected of the "neglected tropical diseases."…”
Section: Introductionmentioning
confidence: 99%